Occurrence Download - GBIF.Org User (The Global Biodiversity Information Facility, 2018)
A dataset containing 10595060 species occurrences available in GBIF matching the query: { "and" : [ { "or" : [ "BasisOfRecord is Specimen", "BasisOfRecord is Human Observation" ] }, "HasCoordinate is true", "TaxonKey is Fabaceae", "HasGeospatialIssue is false" ] } The dataset includes 10595060 records from 2056 constituent datasets; see https://api.gbif.org/v1/occurrence/download/0016454-181108115102211/datasets/export for details. Data from some individual datasets included in this download may be licensed under less restrictive terms.
Keywords: GBIF; biodiversity; species occurrences